2021
DOI: 10.1007/s00421-021-04874-3
|View full text |Cite
|
Sign up to set email alerts
|

Bi-exponential modelling of $$W^{^{\prime}}$$ reconstitution kinetics in trained cyclists

Abstract: Purpose The aim of this study was to investigate the individual $$W^{^{\prime}}$$ W ′ reconstitution kinetics of trained cyclists following repeated bouts of incremental ramp exercise, and to determine an optimal mathematical model to describe $$W^{^{\prime}}$$ W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…That the mean power output of recoveries at 50% of FTP (MOD) and self-selected intensities were not different explains the similar power outputs generated during the subsequent severe intervals; however, the manner of the self-selected recoveries was markedly different to that of the constant MOD recovery condition; power output was initially reduced before increasing as the recovery phase progressed. This pattern is consistent with recent suggestions of the occurrence of a bi-exponential recovery of W′ [ 17 , 20 ] in which a fast component is highly dependent upon the first 30 s of recovery [ 17 ]. This fast recovery phase shares a similar time course to that of PCr restoration [ 47 ] and is likely facilitated by the low power outputs at the outset of the MOD recoveries, given that PCr restoration has been shown to be greatest during passive recovery [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…That the mean power output of recoveries at 50% of FTP (MOD) and self-selected intensities were not different explains the similar power outputs generated during the subsequent severe intervals; however, the manner of the self-selected recoveries was markedly different to that of the constant MOD recovery condition; power output was initially reduced before increasing as the recovery phase progressed. This pattern is consistent with recent suggestions of the occurrence of a bi-exponential recovery of W′ [ 17 , 20 ] in which a fast component is highly dependent upon the first 30 s of recovery [ 17 ]. This fast recovery phase shares a similar time course to that of PCr restoration [ 47 ] and is likely facilitated by the low power outputs at the outset of the MOD recoveries, given that PCr restoration has been shown to be greatest during passive recovery [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…This fast recovery phase shares a similar time course to that of PCr restoration [ 47 ] and is likely facilitated by the low power outputs at the outset of the MOD recoveries, given that PCr restoration has been shown to be greatest during passive recovery [ 48 ]. It has been suggested that the slow recovery phase of the bi-exponential model is linked to the removal of the accumulated metabolites such as lactate, inorganic phosphates and hydrogen ions [ 17 ]. Interestingly, no participants in the present study chose passive rest during any point of their self-selected recoveries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations